Analisis Kemampuan Pemecahan Masalah Siswa dalam Menyelesaikan Soal Berbasis HOTS pada Materi Perbandingan Kelas VII di Darul Ulum Budi Agung Medan - Lubis, Annisa Putri; Indriani, Dea; Ulfa, Syarifah Widya (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to describe students' problem solving abilities in solving HOTS-based questions on the compared material. The method that will be used is a qualitative descriptive method with a scientific approach. The subjects in this research were MTs Darul Ulum Budi Agung students with the sample used being 35 class VII 5 students. The data collection technique used a problem solving ability test instrument in solving HOTS-based mathematics questions on comparable material. There are three stages of data analysis techniques, namely checking the results of students' answers, presenting test data, and drawing conclusions from the research results. The results obtained in this research were the percentage of achievement of students' problem solving abilities. At the understanding the problem stage it was 67%, at the planning completion stage it was 53%, at the plan implementation stage it was 50%, and at the re-examination stage it was 43%. This shows that students' mathematical problem solving abilities in solving HOTS-based questions are in the medium category.